The Influence of Consumer Knowledge, Product Quality, on The Murabahah Financing Decision Process of Islamic Banks and Its Impact on Satisfaction - Todhi Arkhamaya; Ahmad Saeed Abdulraheem (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
Indonesia is the nation with the biggest Muslim populace within the world, and Yogyakarta is one of the areas with the biggest Muslim populace in Indonesia. This consider points to supply data on the quality of Islamic Bank items and information on murabahah contracts for financing choices and their impact on the fulfillment of the Muslim community within the city of Yogyakarta. Information were collected through a survey strategy on 150 respondents employing a purposive testing strategy to decide the respondents' reactions to each variable. At that point an investigation was carried out on the information gotten within the shape of quantitative investigation and subjective examination. The data investigation strategies utilized are different direct relapse examination and basic relapse which work to demonstrate the inquire about theory. Within the different direct relapse test, information that has met the legitimacy test, unwavering quality test, and classical presumption test are handled to deliver an investigation that item quality variables and information have a positive and critical impact on the Acquiring Choice prepare. Whereas in straightforward relapse, it produces an investigation that obtaining choices have a positive and noteworthy impact towards Client Fulfillment.